2020
DOI: 10.1093/abm/kaaa013
|View full text |Cite
|
Sign up to set email alerts
|

An Avatar-Led Intervention Promotes Smoking Cessation in Young Adults: A Pilot Randomized Clinical Trial

Abstract: Background Smoking remains a global concern, especially for young adults. There is a dearth of smoking cessation programs for this population, who seldom seek help or are motivated to quit. Purpose This pilot study assessed the effectiveness of a digital avatar-led Acceptance and Commitment Therapy (ACT) smoking cessation program (Flexiquit) for young adult smokers at all levels of motivation to quit. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…The importance of social support needs to be made clear to the public and to the degree possible mechanisms that can contribute to social support should be supported. Further, psychological flexibility is a trainable set of skills that has repeatedly been shown to ameliorate suffering [22,39]; and can be widely distributed with modern technological intervention tools such as digital, internet, or virtual means [40]. We do not claim, however, that psychological flexibility is the only factor that can be used for interventions.…”
Section: Plos Onementioning
confidence: 92%
“…The importance of social support needs to be made clear to the public and to the degree possible mechanisms that can contribute to social support should be supported. Further, psychological flexibility is a trainable set of skills that has repeatedly been shown to ameliorate suffering [22,39]; and can be widely distributed with modern technological intervention tools such as digital, internet, or virtual means [40]. We do not claim, however, that psychological flexibility is the only factor that can be used for interventions.…”
Section: Plos Onementioning
confidence: 92%
“…It is worth noting that study participants’ readiness to quit smoking at baseline spanned the full range of the Contemplation Ladder, from 0 to 10, suggesting that even sexual and gender minority young adults with very low motivation to quit may be willing to engage with, and may benefit from, an intervention that is designed for smokers at all levels of quit readiness. This was the case in the original Flexiquit trial, where a 29% quit rate was obtained even though 65% of the sample reported low readiness to quit at baseline [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Empowered, Queer, Quitting, and Living (EQQUAL) program is a cultural, linguistic, and sexual and gender minority–targeted adaptation of Flexiquit, a web-based acceptance and commitment therapy (ACT) program designed for young adults at all stages of readiness to quit tobacco use [ 7 ]. In addition to focusing on increasing acceptance of smoking triggers and facilitating values-guided action as cessation treatment mechanisms, ACT also teaches generalizable emotion regulation skills that can increase resilience and buffer minority stress [ 8 ] among sexual and gender minority young adults.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations